2022
DOI: 10.1161/jaha.121.023472
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate TASK‐1 and Are Linked to Myocardial Dilatation in Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. However, underlying molecular mechanisms are insufficiently understood. Previous studies suggested that microRNA (miRNA) dependent gene regulation plays an important role in the initiation and maintenance of AF. The 2‐pore‐domain potassium channel TASK‐1 (tandem of P domains in a weak inward rectifying K + channel–related acid sensitive K + chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Other miRNAs differentially expressed in both human induced pluripotent stem cells (hiPSCs) and atrial tissue samples from AF patients have been recently evaluated [ 98 ]. In particular, miR-34a regulates atrial TASK-1 (tandem of P-domains in a weak inward rectifying K + channel- related acid sensitive K + channel 1) potassium channels and has been proposed as an important contributor to the initiation and maintenance of AF, linked to myocardial dilation.…”
Section: Mirnas Involved In Afib Ed and Af And Their Putative Role As...mentioning
confidence: 99%
“…Other miRNAs differentially expressed in both human induced pluripotent stem cells (hiPSCs) and atrial tissue samples from AF patients have been recently evaluated [ 98 ]. In particular, miR-34a regulates atrial TASK-1 (tandem of P-domains in a weak inward rectifying K + channel- related acid sensitive K + channel 1) potassium channels and has been proposed as an important contributor to the initiation and maintenance of AF, linked to myocardial dilation.…”
Section: Mirnas Involved In Afib Ed and Af And Their Putative Role As...mentioning
confidence: 99%
“…Furthermore, the breathing stimulant compound doxapram inhibits human TASK-1 and TASK-3 channels with equal potency and can be used in a novel pharmacological strategy for cardioversion of acute episodes of paroxysmal AF as well as the rhythm control of persistent AF [ 47 ]. Several other experiments have also shown that the targeted inhibition of TASK-1 channels can effectively treat AF, confirming that it is an antiarrhythmic target in general [ 48 , 49 , 50 , 51 ]. In addition to the regulation of vascular tone in pulmonary arteries, TASK-1 channels also play an important vasomotor role in systemic arteries under specific conditions or at certain stages of ontogenesis.…”
Section: The Biological Roles Of Task Channelsmentioning
confidence: 83%
“…Belevych 2016) revealed experimentally that miRNA-1 drives arrhythmogenesis by altering ion channels and proteins associated with the heart's electrical activity in cardiac diseases [40][41][42][43]. Also, Wiedmann et al [44] aimed to study differential expression of selected miRNA in atrial tissue samples obtained from patients with sinus rhythm, paroxysmal AF, or permanent/chronic AF, and they found that miR-25, miR-21, miR-34a, miR-23a, miR-124, miR-1, and miR-29b upregulation as well as miR-9 and miR-485 downregulation were associated with TASK-1 potassium channel in patients with atrial cardiomyopathy. The above results conclude the disturbance of cardiac ion channel proteins resulting from dysregulated miRNAs may be one of cardiac diseases pathogenesis.…”
Section: Discussionmentioning
confidence: 99%